A QUALITATIVE STUDY OF ASIAN IMMIGRANT-ORIGIN YOUTH’S STRESS FACTORS AND BARRIERS TO SEEKING PROFESSIONAL HELP FOR A MENTAL DISORDER - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Devi, Mairembam Sangita; Devi , Shoraisam Kiranbhala (International Journal of Psychosocial Rehabilitation, 2020)
Immigration-origin youth (IOY) from Asia constitute a substantial and growing portion of the American population (U.S.). Few studies have examined the likely causes of mental health issues in Asian IOY. Although there are low use rates, no research has focused on the Asian IOY’s perspective on mental health care utilization obstacles. An Asian IOY perspective on pressures that may lead to mental health concerns and their difficulties in seeking treatment for such problems was agreed upon via qualitative research. In-depth focus groups with 33 Asian IOYs (n = 33; 58% female) were held to get direct input. The data were examined using a grounded theory method. Pressure to succeed and the stress of being an ethnic minority and an immigrant were among the stressors that Asian IOY experienced, both of which led to their mental health issues. When researchers examined the barriers to Asian IOYs receiving mental health therapy, they considered their parents’ reactions anxiety about treatment and services. Their concerns about stigma, mental health literacy, and practical or logistical reasons for seeking assistance for those with mental health issues. Researchers advocate personalizing outreach programs to persuade more Asian IOY to seek treatment for mental health difficulties.